TEKNIK BIOFLOKULASI Alcaligenes latus PADA INDUSTRI TAPIOKA UNTUK MENGURANGI PENCEMARAN LINGKUNGAN - Retnani, Yuli (Jurnal Rekayasa Lingkungan)
Almost all of the tapioca industries in Bogor are small scale industries and have not implemented the cleaner production practices yet. Results of the survey showed that careless in discharging process of solid and liquid wastes and the absent of waste treatment caused pollution. Utilization of solid waste to handle liquid waste is one of the application of cleaner production. Onggok as solid waste has been utilized to minimize the negative effect of the liquid tapioca waste. It is used as medium of Alcaligenes latus. The microbecan grow well in glucose produce from the onggok in concentration of 5 g/l and fermentation period of 30 days. Treatment with biofloculation reduced liquid waste turbidity by 54%, TSS 60%, BOD by 33%, COD by 34% and cyanide content by 41%. Treatment with biofloculation and dilution reduce turbidity by 89%, TSS by 91%, BOD by 62%, COD by 70% and cyanide content by 78%. Finally, combination of biofloculation, aeration and dilution treatment reduce turbidity by 93%, TSS by 95%, BOD by 71%, COD by 74% and cyanide content by 35%.Key words: biofloculation, solid and liquid waste tapioca, Alcaligenes latus